2017
DOI: 10.1136/jech-2016-208853
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the measurement properties of a Frailty Index across the age spectrum in the Canadian Longitudinal Study on Aging

Abstract: The FI is a feasible method to evaluate frailty and capture frailty-related heterogeneity in populations aged 45-85 years. In this study, the FI had good construct validity in middle-aged and older adults, showing expected correlations with sociodemographic factors consistently across age groups. This method can be easily reproduced in similar datasets, making the FI a generalisable instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
(31 reference statements)
2
25
0
Order By: Relevance
“…Our findings confirm many of our hypotheses and are aligned with the existing literature describing accidental falls, assistive devices, and home care [31][32][33][34]. The increased rate of falls among health conditions (e.g., dizziness or lightheadedness, parkinsonism, etc.)…”
Section: Principal Findingssupporting
confidence: 89%
“…Our findings confirm many of our hypotheses and are aligned with the existing literature describing accidental falls, assistive devices, and home care [31][32][33][34]. The increased rate of falls among health conditions (e.g., dizziness or lightheadedness, parkinsonism, etc.)…”
Section: Principal Findingssupporting
confidence: 89%
“…We showed that individuals who were frail were more likely to have fallen in the past year, and went on to have more falls in the subsequent year. In a mixed sample of community dwelling and older adults resident in long term care in Canada, the FI was also correlated with future falls (r = 0.12; p < 0.001) [53]. In the current study of elderly residents in long term care facilities, the correlation between FI-MDS and prospective falls was slightly stronger (r = 0.21, p = 0.03), perhaps reflecting the higher risk of falls and frailty in general in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The frailty index, multiplied by 100 for easier interpretation (0‐100), was used as the main outcome of interest in this study. The frailty index included 76 potential deficits related to physical function, health and chronic conditions, cognition, activities of daily living, body mass index category, and depression, based on the work of Kanters et al…”
Section: Methodsmentioning
confidence: 97%
“…In older adults, poor oral health has been associated with numerous diseases, including cardiovascular disease, respiratory disease, and diabetes, as well as incident frailty . Frailty is a clinical state in which there is an increase in an individualʼs vulnerability for developing dependency and/or mortality when exposed to a stressor . Increased frailty increases the risk of adverse health outcomes across age‐groups, including falls, hospitalizations, dependency, and death .…”
mentioning
confidence: 99%